Dakwah Multimedia di Situs Jejaring Sosial Facebook - Anshar, Muhammad (Jurnal Komunikasi Islam, 2019)
Abstract: This study discussed the themes of multimedia proselytising on Facebook used by Makassar’s preachers as well as the usage of various forms of multimedia to convey messages to audiences (mad’u) through the Facebook social network. This research was a qualitative study using a content analysis approach. The results of the study stated that the themes conveyed by the preachers were aqidah (faith), sharia (Islamic law), akhlak (manner) morals, mu’amalah (dealings between people), and general messages, such as education, behaviour, and defending the country. While the forms of multimedia proselytising used by da’i (Islamic preachers) were the textual message, images, audio, and video. In addition, da’i needed to improve the quality of material and media da’wa by using information technology through internet media in order to get effective communication (da’wah).